GROWTH AND REGENERATlQN OF AN AQUARIUM-HELD SPINY LOBSTER, PANULIRUS POIYPHAGUS (HERBST) (CRUSTACEA: DECAPODA: PALINURIDAE) - Kathirvel, M (Indian Journal of Fisheries, 2011)
The occurrence of post-larvae and juveniles of the marine spiny lobster,Panulirus polyphagus (Herbst) in Cochin backwaters during October to April-May has been reported by Balasubramanyan (1969) and Rao and Kathirvel(1971). While operating a try net for juvenile penaeid prawns, on 28thApril, 1971, a juvenile specimen (88 mm) of P. polyphagus was obtained.The specimen was kept in a bucket containing water from the same area andwas brought to the laboratory where it was transferred to an aquarium (100 cmX 50 cm X 61 cm) containing sea water of salinity 34.2 %o- '^Â® lobster wasregularly fed with minced prawn meat twice daUy and observations were madeon its growth for 31 days after which it died.